El devenir de las prácticas corporales (2011)
ABSTRACT: In this essay a slight historical review of the concept of embodied practice and the purpose is to elucidate the ways in which some authors critically discussed the study of the body in the field of Physical Education and Sport has had a greater prevalence body “organ”. So bodily practices have been reduced to a human, however, recognizes that bodily practices are social and cultural constructions. You need to dot his review because it is recognized that bodily practices are primarily physical symbols are ways of saying the body, ways and means to “use” of the body.